Plan de Comercialización para “Restaurante el Huerto” de la ciudad de Cuenca, Provincia del Azuay. - Proaño Mendoza, Santiago Enrique (2025)
The city of Cuenca offers a wide gastronomy and El Huerto restaurant aims to differentiate itself and attract new customers by offering an added value proposal including organic vegetables in its dishes. Therefore, this study proposes a marketing plan for the restaurant "El Huerto", to strengthen its position in the market of Cuenca, Ecuador. Among the findings, issues such as the lack of a business philosophy, absence of advertising strategies and a limited digital presence were defined. Through SWOT analysis, surveys and interviews, the public's interest in healthy and sustainable options, such as dishes prepared with organic vegetables, was highlighted. The plan includes strategies such as creating a corporate image using digital marketing and modernizing the restaurant's physical space, which will improve its competitiveness and increase its customer base.